Math, asked by jjjvsvew, 1 year ago

1. Verify the following:
a. (-22) × [(-4) + (-5)]=[(-22) × (-4)] + [(-22) × (-5)]
b. (-12) × [(3) + (-9)]=[(-12) × (4)] + [(-12) × (-9)]
PLEASE HELP ME AND SOLVE THIS
I WILLL MARK YOUR ANSWER AS THE BRAINLIEST

Answers

Answered by Gaikwadtanmayee
21

Step-by-step explanation:

a.) ( - 22 ) × [ ( - 4 ) + ( - 5 ) ] = [ ( -22 ) × ( - 4 ) +[ ( -22 × (-5 ) ]

( -22 ) × [ - 4 - 5 ] = [ ( 88 ) ] + ( 110 )

-22 × -9 = 88 + 110

198 = 198

b.) (-12)×[(3)+(-9)] = [(-12)×(4)] + [(-12)×(-9)

-12×3-9 = -12×4+[(-12)×(-9)]

-12×3-9 = -48+(108)

-12×-6 = -4+108

72= 104

Answered by tyagiosho
3

Answer:

a.) ( - 22 ) × [ ( - 4 ) + ( - 5 ) ] = [ ( -22 ) × ( - 4 ) +[ ( -22 × (-5 ) ]

( -22 ) × [ - 4 - 5 ] = [ ( 88 ) ] + ( 110 )

-22 × -9 = 88 + 110

198 = 198

b.) (-12)×[(3)+(-9)] = [(-12)×(4)] + [(-12)×(-9)

-12×3-9 = -12×4+[(-12)×(-9)]

-12×3-9 = -48+(108)

-12×-6 = -4+108

72= 104

Step-by-step explanation:

Similar questions